The Effectiveness of Classroom Guidance with Problem-based Learning and Jigsaw Techniques to Improve Negative Attitudes towards Premarital Sexual Behavior (Jurnal Bimbingan Konseling, 2020)
This study aimed to analyze classroom guidance with PBL and jigsaw techniques to improve negative attitudes towards premarital sexual behavior in students. The study used pretest-posttest control group design by involving 54 students of SMK Walisongo Semarang. For more, purposive sampling technique was employed to select 54 students as the experimental subjects who were grouped into two. Each contained 27 students. The results of wilcoxon analysis showed that the experimental group treated using PBL technique experienced improvement on the negative attitudes toward premarital sexual behavior (Z = -4.54; p < 0.05), while Jigsaw technique gained (Z = -4.54; p < 0.05). Furthermore, the kruskal wallis test results showed that the PBL technique gained (Z(18) = 14.872; p > 0.05) and the jigsaw technique gained (Z(18) = 14.872; p > 0.05). These findings provide understanding for counselors that conducting classroom guidance with PBL and jigsaw techniques can improve negative attitudes toward premarital sexual behavior in students.